EVALUATION OF THE MEDICINAL PROPERTIES OF THE PLANT CENTIPEDE BASED ON ITS CHEMICAL COMPOSITION - Ibrohim Rahmonovich Askarov; Azizbek Sobirovich Khojikulov; Oinurakhon Khusniddin kizi Abdusalomova (Scholars Digest Publishing, 2025)
The article presents information on the botanical description of the centipede plant, its geographical distribution, chemical composition, and importance for human health, as well as an analysis of the content of water-soluble vitamins and flavonoids in the plant extract using the HPLC method.
Keywords: Centipede plant, equiseton saponin, flavonoids, vitamin C-carotene, acids, water-soluble silicates, organic compounds, preservatives vitamin B6, vitamin B2, vitamin B3, water and alcohol extract, salicylic acid and quercetin.